Institutional Model of The National Legislative Body: Smart Regulations and Regulatory Guillotine as Solutions to Hyper-Regulation in Indonesia - Fahri Bachmid (Badan Strategi Kebijakan Hukum, 2025)
This study aims to analyze the institutional design of regulatory management bodies in various countries and assess their applicability to the Indonesian context, particularly in overcoming hyper-regulation and regulatory disharmony. The study formulates strategic recommendations to establish a centralized regulatory agency to streamline the legislative process and improve cross-sector coordination. Using a qualitative embedded case study approach, the research combines a systematic literature review and comparative analysis focused on institutional structure and implementation outcomes, enriched by triangulation of Indonesian regulatory data: The study identified that in Indonesia, the fragmentation of 3,618 central regulations and 15,982 regional regulations emphasizes the urgency of establishing a National Legislation Agency (BLN) to consolidate authority, eliminate redundancies, and implement ex post evaluation. The findings recommend legal reforms to establish a National Legislation Agency by transforming (Badan Pembinaan Hukum Nasional – BPHN) into BLN or establishing a new agency. The implications of the main policy include, enactment of the regulatory alignment law that adopts the one in, two out principle, the establishment of a regulatory sandbox for policy trials in priority sectors, and increased bureaucratic capacity through training based on international best practices.